Ferroptosis-based drug delivery system as a new therapeutic opportunity for brain tumors - Yao, Yansheng; Ji, Peng; Chen, Hao; Ge, Jianwen; Xu, Yajing; Wang, Peng; Xu, Li; Yan, Zhirong (Frontiers in Oncology, 2023)
The brain tumor is a kind of malignant tumor with brutal treatment, high recurrence rate, and poor prognosis, and the incidence and death rate is increasing yearly. Surgery is often used to remove the primary tumor, supplemented by radiotherapy and chemotherapy, which have highly toxic side effects. Therefore, there is an urgent need to explore new strategies, methods, and technologies that can genuinely improve the treatment of brain tumors. Ferroptosis differs from traditional apoptosis's morphological and biochemical characteristics, and ferroptosis possesses its unique characteristics and mechanisms, opening up a new field of ferroptosis treatment for cancer. It has been found that there is a close relationship between ferroptosis and brain tumors, and a novel nano-drug delivery system based on ferroptosis has been used for the ferroptosis treatment of brain tumors with remarkable effects. This review firstly analyzes the characteristics of ferroptosis, summarizes the mechanism of its occurrence and some factors that can be involved in the regulation of ferroptosis, introduces the potential link between ferroptosis and brain tumors, and clarifies the feasibility of ferroptosis in the treatment of brain tumors. It then presents the ferroptosis nano drug delivery systems developed under different metabolic pathways for ferroptosis treatment of brain tumors. Finally, it summarizes the current problems and solutions of ferroptosis nano drugs for brain tumor treatment, aiming to provide a reference for developing ferroptosis nano drugs against brain tumors.